2021
DOI: 10.3389/fonc.2021.676077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Sirtuin 3 Causes Alterations of Key Metabolic Regulators in Melanoma

Abstract: The mitochondrial sirtuin SIRT3 plays key roles in cellular metabolism and energy production, which makes it an obvious target for the management of cancer, including melanoma. Previously, we have demonstrated that SIRT3 was constitutively upregulated in human melanoma and its inhibition resulted in anti-proliferative effects in vitro in human melanoma cells and in vivo in human melanoma xenografts. In this study, we expanded our data employing knockdown and overexpression strategies in cell culture and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…In addition, the experimental overexpression of SIRT3 via plasmids in Hs294T human melanoma cells and immortalized melanocytes led to both enhanced proliferation and colony formation in the melanoma cells and increased proliferation in melanocytes, evidence of the role of SIRT3 in melanoma growth [33]. This result was supported by observations that tumors with an induced overexpression of SIRT3 in mouse xenograft tumors had increased tumorigenicity [153]. Furthermore, short hairpin RNA knockdown of SIRT3 in melanoma led to favorable effects including reduced cell proliferation and migration, indicating possible therapeutic options [33].…”
Section: Sirt3-inducing Oxidative Phosphorylation In Melanoma Cellsmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, the experimental overexpression of SIRT3 via plasmids in Hs294T human melanoma cells and immortalized melanocytes led to both enhanced proliferation and colony formation in the melanoma cells and increased proliferation in melanocytes, evidence of the role of SIRT3 in melanoma growth [33]. This result was supported by observations that tumors with an induced overexpression of SIRT3 in mouse xenograft tumors had increased tumorigenicity [153]. Furthermore, short hairpin RNA knockdown of SIRT3 in melanoma led to favorable effects including reduced cell proliferation and migration, indicating possible therapeutic options [33].…”
Section: Sirt3-inducing Oxidative Phosphorylation In Melanoma Cellsmentioning
confidence: 76%
“…Furthermore, SIRT3 has a general role in maintaining functional metabolism, as the knockdown of SIRT3 led to alterations in genes for multiple biochemical pathways, including glycolysis, the citric acid cycle, and the pentose phosphate pathway [153]. One key function of SIRT3 is reduction in ROS via the detoxification enzyme manganese superoxide dismutase 2 (SOD2).…”
Section: Sirt3-inducing Oxidative Phosphorylation In Melanoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis we have found inconsistent finding with state of downstream molecule (yellow lines present in Fig 9 ). We would like to emphasize that the inconsistencies were also observed by other scientist when IPA was applied for cancer proteome analysis [ 58 63 ].…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies showed an increase in “spare respiratory capacity” of melanoma cells—the mitochondrial capacity to meet extra energy requirements, beyond the basal level, which occurred in response to acute cellular stress or heavy workload [ 45 ]. In particular, this occurs due to activation of PGC1α-dependent mitochondrial biogenesis, regulation of activity of enzymes involved in the respiratory chain by Sirtuin-3 directly and through an increased activity of the antioxidant enzyme SOD2, required for maintenance of spare respiratory capacity [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%